Advances in the diagnosis of GERD - Săraru Elena-Roxana; Enciu Vlad; Peagu Razvan; Fierbinţeanu-Braticevici Carmen (Sciendo, 2021)
Gastroesophageal reflux disease (GERD) is considered one of the most frequent chronic gastrointestinal diseases globally with high costs due to treatment and investigations.